2004
DOI: 10.1007/s10142-004-0104-3
|View full text |Cite
|
Sign up to set email alerts
|

Genes controlling seed dormancy and pre-harvest sprouting in a rice-wheat-barley comparison

Abstract: Pre-harvest sprouting results in significant economic loss for the grain industry around the world. Lack of adequate seed dormancy is the major reason for pre-harvest sprouting in the field under wet weather conditions. Although this trait is governed by multiple genes it is also highly heritable. A major QTL controlling both pre-harvest sprouting and seed dormancy has been identified on the long arm of barley chromosome 5H, and it explains over 70% of the phenotypic variation. Comparative genomics approaches … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
90
0
2

Year Published

2010
2010
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 151 publications
(92 citation statements)
references
References 25 publications
0
90
0
2
Order By: Relevance
“…This region showed good synteny with terminal end of long arm of rice chromosome 3 and with the telomeric region of wheat chromosome 4AL. However, this region was located outside the QTL reported for seed dormancy in wheat on 4AL (Li et al, 2004). On the basis of available markers, the most likely position of the QTL for PHST/seed dormancy was identified in bin 4AL12-0.43-0.59 on 4AL (Li et al, 2004).…”
Section: G E N E T I C S P R O V I S I O N a L P U B L I S H I N Gmentioning
confidence: 87%
See 2 more Smart Citations
“…This region showed good synteny with terminal end of long arm of rice chromosome 3 and with the telomeric region of wheat chromosome 4AL. However, this region was located outside the QTL reported for seed dormancy in wheat on 4AL (Li et al, 2004). On the basis of available markers, the most likely position of the QTL for PHST/seed dormancy was identified in bin 4AL12-0.43-0.59 on 4AL (Li et al, 2004).…”
Section: G E N E T I C S P R O V I S I O N a L P U B L I S H I N Gmentioning
confidence: 87%
“…However, this region was located outside the QTL reported for seed dormancy in wheat on 4AL (Li et al, 2004). On the basis of available markers, the most likely position of the QTL for PHST/seed dormancy was identified in bin 4AL12-0.43-0.59 on 4AL (Li et al, 2004). When we compare this region with the 4AL dense map of present study, it was found that MQTL 8 (located at 75.75 cM) was present in the same region, thus suggesting the possibility of GA20-oxidase gene (TaGA20-ox1) to be a candidate for PHST/seed dormancy on 4AL.…”
Section: G E N E T I C S P R O V I S I O N a L P U B L I S H I N Gmentioning
confidence: 87%
See 1 more Smart Citation
“…In this study, seven gene-specific markers were developed from six barley EST sequences using a comparative strategy, which significantly narrowed the region of the BVP-1 gene. In previous research, a comparative genomic strategy was used to identify and clone target genes in barley ( Li et al 2004;Jia et al 2009;Liu et al 2011;Ye et al 2011;Silvar et al 2012) and in wheat (Valá rik et al 2006;Kuraparthy et al 2008;Faricelli et al 2010). …”
Section: Discussionmentioning
confidence: 99%
“…The major QTL for grain dormancy in wheat, which is on chromosome 4AL, explains up to 40% of the phenotypic variability in some populations. The gene underlying the QTL has not been identified but it is thought to be syntenic with the barley SD2 dormancy QTL (Li et al, 2003) on chromosome 5HL Zhang et al, 2008). The cloning of this major QTL will be an important step in providing wheat and barley breeders with new opportunities to increase dormancy in new cultivars.…”
Section: Practical Implications Of Knowledge About Dormancy In Cerealsmentioning
confidence: 99%